New Eastern European Immigrants in the United States - Michalikova, Nina (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2017)
This book deftly extends previous research on post-1965 immigration to the United States in order to examine the cultural, socioeconomic, structural, and political adaptation of Eastern European immigrants after 1991. Also, the book engages in a systematic examination of adaptation experiences through the lenses of existing theories of adaptation, and fills a gap in the literature on this understudied immigrant population. Using the latest quantitative data, Nina Michalikova contributes to the field of immigration studies by revealing the diverse adaptation experiences of contemporary American immigrants through cross-country and cross-group comparisons. .